Anatomia do nervo isquiático em mocós (Kerodon rupestris WIED, 1820) aplicada a clínica de animais silvestres - Dos Santos, Renata Celis; de Albuquerque, José Fernando Gomes; Silva, Márcio César Vasconcelos [UNESP]; de Moura, Carlos Eduardo Bezerra; Chagas, Roberto Sergio Nunes; Barbosa, Roméria Rodrigues [UNESP]; Miglino, Maria Angélica (My University, 2006)
To know the origin of the ischiatic nerve in mocos (Kerodon rupestris Wied,1820) near by intervertebral forames and the muscling belonging to its routes were used 10 adult animals, from CEMAS-ESAM. After natural obit, they were fixed in formol (10%) and dissected to exposition and to singt of the ischiatic nerve. The results were indicated in percentage. Variations in the quantity of the lumber and sacral vertebras nere observed, five animals (50,00%) reveled seven lumbar vertebras and three sacral ones; two animals recrealed seven lumbar vertebras and four sacral ones, and two animals reveled six lumbar vertebras and three sacral ones. An animal (10,00%) revealed six lumbar vertebras and four ones. Therefore, the origin of the nerve was differentiated five animals (50,00%) had the participation of L 7,S 1,S 2; two animals (20,00%) with L 7,S 1; and a little part of S 2. Two animals (20,00%) with L 6,S 1,S 2, and an animal (10,00%) with L 6,S 1, and a little part of S 2. The last root of the ischiatic nerve in all its origins, contribute to the constitution of the first root of pudental nerve. It was verified that in all its route, the ischiatic nerves (100,00%) ceded branches to the muscles: medial gluteus, deep gluteus, superficial gluteus, emiting muscular branches to the femoral biceps or to thigh, and to the semimembranous and semi-tendinous muscles, that is continuous with a high calibre trunk, originating the fibular nerve(sideways), the tibial nerve(medial) and the lateral plantar sural cutaneous nerve (caudal).
Ischiatic nerve anatomy in mocós (Kerodon rupestris WIED, 1820) applicable to clínic of wild animals
Keywords: Anatomy; Ischiatic nerve; Kerodon rupestris; Animalia